2008
DOI: 10.1177/1076029607304405
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Induced Thrombocytopenia Complicating Hemodialysis

Abstract: Hemodialysis complicated by heparin-induced thrombocytopenia (HIT) is a rare event requiring anticoagulation with direct-thrombin inhibitors. Contaminant calcific uremic arteriolopathy (calciphylaxis) further complicates this situation due to the possibility that warfarin anticoagulation may exacerbate skin necrosis. The authors report a patient with renal failure and calciphylaxis who developed HIT after starting hemodialysis. She was successfully treated with Argatroban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…We identified nonrandomized studies evaluating the use of argatroban, danaparoid, fondaparinux, bivalirudin, and rivaroxaban. Ten studies reported on treatment with argatroban, [111][112][113][114][115][116][117][118][119][120] 3 studies reported on treatment with danaparoid, 70,121,122 3 studies reported on treatment with fondaparinux, [123][124][125] 2 studies reported on treatment with bivalirudin, 57,126 and 1 study reported on treatment with rivaroxaban. 127 These studies reported on the outcomes of bleeding, thromboembolic events, mortality, and serious adverse events.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified nonrandomized studies evaluating the use of argatroban, danaparoid, fondaparinux, bivalirudin, and rivaroxaban. Ten studies reported on treatment with argatroban, [111][112][113][114][115][116][117][118][119][120] 3 studies reported on treatment with danaparoid, 70,121,122 3 studies reported on treatment with fondaparinux, [123][124][125] 2 studies reported on treatment with bivalirudin, 57,126 and 1 study reported on treatment with rivaroxaban. 127 These studies reported on the outcomes of bleeding, thromboembolic events, mortality, and serious adverse events.…”
Section: Remarkmentioning
confidence: 99%
“…Among 97 patients with HIT who received argatroban, 18 deaths were reported; however, none were the result of thrombosis. [111][112][113][114][115][116][117][118][119][120] One patient with peripheral vascular disease underwent amputation, and 3 patients developed thrombotic events. Major bleeding occurred in 3 of 50 treatment courses in 1 study and in 2 of 30 patients in another study.…”
Section: Remarkmentioning
confidence: 99%
“…Several recent publications have reported a higher occurrence of HIT in patients treated with contaminated heparin. 25,26 The hypersulfated glycosaminoglycans such as the pentasaccharide polysulfate also produce a much higher incidence of HIT. The main contaminant in recalled heparin is identified to be oversulfated chondroitin sulfate (OSCS), 27 the same compound known to have caused several deaths due to generation of bradykinin, a potent vasoactive mediator, and generation of C3a and C5a, potent anaphylatoxins derived from complement proteins.…”
Section: Frequency Of Hitmentioning
confidence: 99%
“…These direct factor inhibitors have a different mechanism of action than warfarin or the activation of antithrombin III by heparins. Anticoagulation of a patient with calciphylaxis with argatroban has been reported, but use of DOACs in calciphylaxis is not well described in the literature.…”
Section: Introductionmentioning
confidence: 99%